الجهود الدعوية في منطقة وادي سوف الشيخ البخاري عوينات – - بنين, رجاء; حساني, صبرينة (جامعة الوادي university of eloued, 2016)
يقوم هذا البحث بدراسة: "الجهود الدعوية في منطقة وادي سوف الشيخ البخاري عوينات أنموذجا"، وقد انبنى على مبحثين، وخاتمة؛ حيث خُ صّ ص المبحث الأول لدراسة مفهوم الدعوة، والتعريف بمنطقة وادي سوف، ثم نبذة تاريخية عن الحركة الدعوية في المنطقة، ثم جاء المبحث الثاني لدراسة حياة الشيخ البخاري عوينات وجهوده الدعوية . وقد خلص البحث إلى جملة من النتائج كان من أهمها الآتي: أنّ الدعوة هي دين الله الذي بعث به الأنبياء عليهم الصلاة والسلام لتبليغ الإسلام وبجميع الوسائل والأساليب التي تتنسب مع أحول المدع وين، والزاد العلمي والتفقه في الدين من أهم الجهود الإصلاحية والدعوية التي ارتكز عليها الشيخ البخاري عوينات. Abstract This study examines the advocacy efforts in the area of Wadi Suf Sheikh Bukhari Awainat model, has been identified from the two studies and the conclusion of the first section to study the concept of advocacy and the definition of Wadi Suf and then a historical overview of the advocacy movement in the region and then came the second study of the life of Sheikh Bukhari Awainat and his efforts advocacy. The research summarized a number of results, the most important of which were: -The call is the religion of Allah, which was sent by the prophets peace be upon them to inform Islam and by all means and methods that belong with the turn of the invitees. -Understanding in religion and fatwa and learning the forensic science of the most important reform efforts advocacy Sheikh Bukhari Awainat.
دعوة